A NIR machine for moisture content measurements of forest biomass in frozen and unfrozen conditions. Issue 1 (2nd January 2017) - Fridh, Lars; Volpé, Sylvain; Eliasson, Lars
ABSTRACT: Moisture content (M) is an important quality parameter of wood chips, strongly influencing the net calorific value as received. The current standard for determining M, the oven-drying method, is slow and sometimes the sampled lot is combusted before the determination is concluded. This increases the risk of inefficient combustion and reduces the value of M determination. In Scandinavia, winter biomass supply operations are the major source of forest biomass chips to the heating plant and frozen chips are commonly delivered. Comparisons were made between the Prediktor Spektron Biomass, which measures M by near-infrared (NIR) spectroscopy, and the oven-drying method. M measurements were carried out for a total of four biomass materials in both frozen and unfrozen condition, where M ranged from 24% to 65% wet basis. On average the machine underestimated M by 0.34%-units for frozen materials and overestimated M by 0.68%-units for unfrozen materials. The results for repeatability of measurements showed that 95% of the measurements were within ±2.24%-units of the mean for the frozen materials and within ±1.72%-units for the unfrozen. This shows that the machine was suited to measure unfrozen and frozen material, and allows the measurement of bulky samples and isn't constrained by particle size.